The use of behaviour change theories and techniques in research-informed coach development programmes: a systematic review - Allan, V.; Vierimaa, M.; Gainforth, H. L.; Côté, J. (International Review of Sport and Exercise Psychology, 2018)
Coaches are often targeted in interventions to enhance athlete outcomes. While coach development programmes (CDPs) may change coach behaviour, little is known about theories and techniques used to design and implement effective programmes. Examining the use of behaviour change theories and techniques (BCTs) can aid in understanding and improving CDPs. Adhering to PRISMA guidelines, the purpose of this research was to conduct a systematic review examining the use of behaviour change theories and BCTs in CDPs. In total, 29 CDPs met the inclusion criteria. Data were extracted using the Theory Coding Scheme and Behaviour Change Technique Taxonomy (v1). Only six CDPs were explicitly based on behaviour change theory, and no single theory or combination of theories was used more than once. The number of BCTs used per CDP ranged between one and nine. There was no significant difference between theory-based and non-theory-based CDPs concerning the number of BCTs used per CDP. Theoretical frameworks and techniques that have the potential to effectively change coach behaviours are not being used frequently or consistently in the design and implementation of CDPs. To design CDPs that change coach behaviours and facilitate positive outcomes, further research examining theoretical influences on coach behaviours is needed.